Beowulf and other Old English poems - Williamson, Craig, 1943-; Williamson, Craig, 1943-; Shippey, T. A. (Middle Ages series., 2011)
Overview: The best-known literary achievement of Anglo-Saxon England, Beowulf is a poem concerned with monsters and heroes, treasure and transience, feuds and fidelity. Composed sometime between 500 and 1000 C.E. and surviving in a single manuscript, it is at once immediately accessible and forever mysterious. And in Craig Williamson's splendid new version, this often translated work may well have found its most compelling modern English interpreter. Williamson's Beowulf appears alongside his translations of many of the major works written by Anglo-Saxon poets, including the elegies "The Wanderer" and "The Seafarer," the heroic "Battle of Maldon," the visionary "Dream of the Rood," the mysterious and heart-breaking "Wulf and Eadwacer," and a generous sampling of the Exeter Book riddles. Accompanied by a foreword by noted medievalist Tom Shippey on Anglo-Saxon history, culture, and archaeology, and Williamson's introductions to the individual poems as well as his essay on translating Old English, the texts transport us back to the medieval scriptorium or ancient mead hall to share an exile's lament or herdsman's recounting of the story of the world's creation. From the riddling song of a bawdy onion that moves between kitchen and bedroom, to the thrilling account of Beowulf's battle with a treasure-hoarding dragon, the world becomes a place of rare wonder in Williamson's lines. Were his idiom not so modern, we might almost think the Anglo-Saxon poets had taken up the lyre again and begun to sing after a silence of a thousand years.